2014
DOI: 10.1016/j.drugalcdep.2014.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of waterpipe smoking initiation among school children in Irbid, Jordan: A 4-year longitudinal analysis

Abstract: Objective Guided by the Attitude-Social influence-self Efficacy (ASE) theory, this study identified predictors of waterpipe (WP) smoking initiation in a WP naïve cohort of Jordanian schoolchildren. Methods A school-based cohort of all 7th grade students (N=1,781) in 19 of 60 schools in Irbid, Jordan, was followed from 2008 to 2011. Generalized linear mixed modeling was used to examine predictors of WP initiation among WP-naïve students (N=1,243). Results During the 3-year study, WP initiation was documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 84 publications
4
27
1
Order By: Relevance
“…Contrary to this observation, youth who were physically active were more likely to report smoking a waterpipe than those who were not physically active (Primack et al, 2010). Moreover, higher physical activity was a predictor of initiation (McKelvey et al, 2014) and progression (Jaber et al, 2015b) on waterpipe smoking among a cohort of schoolchildren in Jordan (median age≈13 years at baseline). In line with these findings, our study shows that youth who are physically active are more likely to loss autonomy over waterpipe smoking.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Contrary to this observation, youth who were physically active were more likely to report smoking a waterpipe than those who were not physically active (Primack et al, 2010). Moreover, higher physical activity was a predictor of initiation (McKelvey et al, 2014) and progression (Jaber et al, 2015b) on waterpipe smoking among a cohort of schoolchildren in Jordan (median age≈13 years at baseline). In line with these findings, our study shows that youth who are physically active are more likely to loss autonomy over waterpipe smoking.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, previous studies among Middle Eastern youth showed that having a sibling who smokes a waterpipe was a predictor of initiation (McKelvey et al, 2014) and higher use (Jaber et al, 2015b) of a waterpipe. In line with these findings, waterpipe smokers in this study who have at least one sibling who smokes a waterpipe were twice as likely to become addicted to a waterpipe.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The current waterpipe smoking rate was low among students in Hong Kong. However, studies from other countries (e.g., the US, Canada and Jordan) suggest that waterpipe smoking may increase rapidly in a short time (Arrazola et al 2015;Czoli et al 2013;McKelvey et al 2014;Minaker et al 2015). Thus waterpipe smoking in Hong Kong might be in the early stage of epidemic, and its potential growth should not be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that having friend/friends who consume waterpipe, plays an important role in smoking in both genders because smoking waterpipe is a social behaviour and often occurs when people are together. 11,[33][34][35] A limited number of studies have examined the psychological characteristics of consumers who wish to quit their waterpipe smoking. 36 Researchers believed that low self-efficacy is a powerful stimulus to smoking waterpipe and high self-efficacy is a personal factor required to cessation.…”
Section: Discussionmentioning
confidence: 99%